INCLUSIVE TOURISM DEVELOPMENT IN MONTENEGRO STAKEHOLDER PERSPECTIVES AND STRATEGIC OPPORTUNITIES FOR LGBTQ+ MARKET GROWTH - Lacmanović, Darko; Raspor, Andrej (Economic Outlook, 2026)
This study examines the potential to develop inclusive tourism in Montenegro, with a specific focus on the LGBTQ+ market segment. Based on a combination of secondary data analysis and primary qualitative research through interviews with key tourism stakeholders, the paper explores current levels of awareness, attitudes, and readiness for engaging with LGBTQ+ tourism. The findings reveal that stakeholders generally recognize the economic and social value of LGBTQ+ tourism, particularly its association with high-spending travelers and destination diversification. However, significant structural and societal barriers remain, including limited institutional support, insufficient legal protections, a lack of targeted strategies, and prevailing social prejudices. Despite these challenges, the research highlights growing openness among tourism providers and identifies opportunities for strategic development through education, infrastructure improvement, and inclusive marketing approaches. The study emphasizes the need for a coordinated, multi-stakeholder strategy to position Montenegro as a welcoming and competitive destination for LGBTQ+ travelers. The paper contributes to the understanding of emerging inclusive tourism markets and provides a foundation for future policy-making and business strategies aimed at fostering sustainable and socially responsible tourism development.
Keywords: LGBTQ tourism, tourist destination, stakeholders, Montenegro